A Retrospective review of medical gastrointestinal endoscopy in children attending Red Cross War Memorial Children’s Hospital, Cape Town - Eke, Christopher Bismarck (Department of Paediatrics and Child Health, 2020)
Background: Gastrointestinal endoscopy has evolved to become an important diagnostic, therapeutic as well as surveillance and follow-up modes of management in children with diverse gastrointestinal diseases. There is a paucity of data on gastrointestinal endoscopy in children in the sub- Saharan African region. The objectives of the study were to describe the socio-demographic characteristics; presenting symptoms; indications; endoscopic yield; impact of endoscopy on management; as well as its safety profile and complications. In addition algorithms for the indications of medical gastrointestinal endoscopy in children were designed using the results derived from the presenting symptoms and indications for gastrointestinal endoscopy among the patients. Methods: This was a cross sectional descriptive study. Subjects were children < 18 years attending Red Cross War Memorial Children’s Hospital (RCWMCH) who underwent medical gastrointestinal endoscopic procedures from 2007 to 2016. Study ethical approval was obtained from University of Cape Town while written permission from the RCWMCH Research and Management Committee prior to the commencement of the study. Data sheet was used in retrieving relevant patients variables from the hospital’s medical records and the Division of Paediatric Gastroenterology endoscopy and laboratory (histopathology) databases. Data was analysed using Stata 13.1. A p- value of less than 0.05 was considered statistically significant. Results: A total of 402 children were studied with 773 endoscopies performed comprising 670 oesophagogastroduodenoscopies (OGD) and 103 colonoscopies. For OGD: 179 (26.7%), 287(42.8%) and 204 (30.4%) procedures were for diagnostic, therapeutic and follow - up indications. A total of 78 (10.1%) combined OGD/colonoscopy were carried out. Out of 103 total colonoscopies performed, 67 (65.0%), 30(29.1%), and 6 (5.8%), were for diagnostic, follow - up and therapeutic indications respectively. vi Feeding difficulty 112 (25.4%) and rectal bleeding 11 (2.7%) were the main presenting symptoms for OGD and colonoscopy respectively. Main diagnostic indications for OGD, combined OGD/colonoscopy and colonoscopy alone respectively were chronic abdominal pain 51 (12.6%) and probable inflammatory bowel disease (IBD) 30 (7.5%) and IBD 30 (7.5%). Change 143 (35.6%)/ insertion 87(21.6%) of percutaneous gastrostomy were the most common therapeutic indications for OGD and polypectomy 8 (2.7%) for colonoscopy. Abnormal (positive) macroscopic findings on endoscopy were reported on 79/179(44.1%), 35/68(51.55%), and 46/67(53.7%) of OGD, combined OGD with lower scope, and colonoscopy alone respectively. Also, positive histological findings on OGD, combined OGD with colonoscopy, and colonoscopy alone were reported in 62/179(34.6%), 34/68(50.0%), and 32/67(47.8%) respectively. The overall normal endoscopic findings (both abnormal macroscopic findings on endoscopy and histological findings) were 63/179(35.3%) and 25/67(37.3%) for OGD and colonoscopy while overall diagnostic (endoscopic) yield was 116/179(64.8%) for OGD and 42/67(62.7%) for colonoscopy respectively. For OGD the main endoscopic yield reported were gastritis in 50(27.9%) and oesophageal varices 31(17.3%) while inflammatory bowel disease (Crohn’s disease 9(13.4%), ulcerative colitis 7(10.4%), juvenile polyps 9(13.4%) and intestinal tuberculosis 7(10.4%) were observed in colonoscopy respectively. A significant impact of endoscopy on the management of subjects were recorded in 298(74.1%) (p < 0.001) including diagnostic (change of medication, addition of new medication) and therapeutic (insertion/change of PEG; sclerotherapy 29 (9.8%) , band ligation of oesophageal varices 28 (9.4%), and polypectomy 8(2.7%)). The overall complication rate was 4.0% (16 patients). Conclusion: Feeding difficulty and rectal bleeding were the most common presenting symptoms for OGD and colonoscopy; with chronic abdominal pain and IBD being the most common indication for performing OGD and colonoscopy respectively. Therapeutic modalities of endoscopy performed were PEG insertion/change, polypectomy, sclerotherapy/band ligation for varices. vii Endoscopic yield was 116/179(64.8%) for OGD and 42/67(62.7%) for colonoscopy respectively a significant impact of endoscopy on the management of subjects were recorded in 298(74.1%) (p < 0.001). No mortalities were recorded following the procedures, however 16(4%) had some complications. Use of societal guidelines in selecting children with appropriate indications for gastrointestinal endoscopy will result in higher diagnostic yield and application of therapeutic modalities in children with gastrointestinal disorders resulting in significant impact on patient’s management and minimize complications.